Facilitators and Barriers of Treatment Compliance among Type 2 Diabetes Mellitus Patients Attending the Diabetes Clinic of a Tertiary Care Hospital, Kolkata: A Mixed- Methods Study - Dey, Abhipsa; Paria, Baishakhi; Mandal, Moumita; Mondal, Aparajita; Bhattacharyya, Nabanita; Basu, Mausumi (Healthline (Gujarat India), 2024)
Introduction: Type 2 diabetes mellitus is a disease of epidemic proportions and has emerged as a major healthcare problem. Compliance to medication plays a crucial role in achieving success in medical treatment and preventing complications. Objective: To assess the treatment compliance among the study participants and explore its perceived barriers and facilitators. Method: A descriptive cross-sectional study was carried out using Morisky’s Medication Adherence Scale (MMAS) among 308 type 2 diabetes mellitus patients who were selected through systematic random sampling. Qualitative data was collected though in-depth interviews and were analysed by manual content analysis Results: Out of the 308 study participants 47% were found to have high treatment compliance and 20% and 35% were found to have medium and low compliance, respectively. On binomial logistic regression, age, duration since diagnosis, family support and current treatment regimen were found to be significantly associated with treatment compliance. Multiple facilitators of compliance could be identified of which, self-awareness of disease, fear of complications and family support were most pronounced. Whereas inability to purchase the medicines, forgetfulness, and lack of satisfaction with health services, were among the identified barriers of treatment compliance. Conclusion: High Compliance to diabetes medication was found among 47% of the study participants. Tailored interventions against the perceived barriers are necessary to promote compliance and improve glycemic control.